The Current Practice of Second Language Learning in Early Childhood Education: Literature Review study - Novitasari, Yesi; Yetti, Elindra; Sumantri, Mohamad Syarif (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
A second language is a language that a person acquires after acquiring his or her mother tongue, even if it is actually the third, fourth, and so on for the purpose of communication, governmental interests, education, and others. This study aims to investigate how second language learning takes place in Early Childhood Education (ECED) using the literature review research method. The literature review for this study was conducted with a systematic and comprehensive approach, aiming to capture various perspectives on second language learning in ECD. The main finding was that the introduction of a second language to young children is widely practiced in countries where English is a second language. Research and information discussions on teaching English to children have grown rapidly in recent years, reflecting the increasing number of young children learning English as a second language around the world in a variety of fun ways and diverse strategies to prepare an adaptable generation for the future.